The making of the slave class - Carrier, Jerry, 1948- (Algora Pub., 2010)
You can only be a king if you have many peasants. You can only have the super-rich if you have many who are poor. And this is the basis for class. A nationally recognized instructor in class, race, American culture, economic development and poverty issues, Jerry Carrier offers the personal story of a working class man's early life in poverty combined with a very cogent dissection of the signals and mechanisms that create and maintain the class system in the United States which determines who will prosper and who will fail.